2013
DOI: 10.1007/s00464-013-2992-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gastrointestinal anastomoses using knotless barbed sutures are safe and reproducible: a single-center experience with 201 patients

Abstract: The use of knotless barbed suture for laparoscopic intestinal anastomosis is safe and reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…In contrast, according to a retrospective study by Choi et al In this trial, barbed suture material (V-Loc) for the repair of uterine wall defects after enucleation of myomas was used in both groups. Barbed suture has been used in a number of conventional laparoscopies using multiple trocars, including hysterectomies (21), colectomies (22), hernia repairs (23), and gastrointestinal anastomoses (24), with good results that greatly facilitate laparoscopic suturing. The use of barbed suture decreases the time required by surgeons for laparoscopic suturing, thereby reducing the total Note: Data are expressed as frequency (percentage), mean AE SD, or median (range), as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, according to a retrospective study by Choi et al In this trial, barbed suture material (V-Loc) for the repair of uterine wall defects after enucleation of myomas was used in both groups. Barbed suture has been used in a number of conventional laparoscopies using multiple trocars, including hysterectomies (21), colectomies (22), hernia repairs (23), and gastrointestinal anastomoses (24), with good results that greatly facilitate laparoscopic suturing. The use of barbed suture decreases the time required by surgeons for laparoscopic suturing, thereby reducing the total Note: Data are expressed as frequency (percentage), mean AE SD, or median (range), as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the efficacy of this new material has been evaluated in different surgical fields, a few general surgery studies are available [12][13][14][15][16][17][18], gynecologists have also demonstrated its utilities [19][20][21], oncologists have reported advantages in its properties [22] and urology is the field where its usefulness is already a standard and concentrates most of its reports [23][24][25][26][27].…”
mentioning
confidence: 99%
“…Further advancements in laparoscopic techniques and instrumentation are necessary for the development of the laparoscopic gastrectomy procedure. Among these developments, the clinical efficacy and suitability of knotless barbed absorbable suture has been reported to facilitate intestinal anastomosis in the past [[15], [16], [17]]. One of these novel sutures, the V-Loc is a self-anchoring unidirectional barbed suture that obviates the need for tying knots.…”
Section: Discussionmentioning
confidence: 99%